Disrupting arrhythmia in a professional male wrestler athlete after rapid weight loss and high-intensity training—Case report - Milovančev, Aleksandra; Miljković, Tatjana; Ilić, Aleksandra; Stojšić Milosavljević, Anastazija; Petrović, Milovan; Roklicer, Roberto; Lakičević, Nemanja; Trivić, Tatjana; Drid, Patrik (Frontiers in Cardiovascular Medicine, 2023)
Physiological heart adaptations may lead to increased susceptibility to arrhythmia in athletes. Furthermore, vigorous training and method like rapid weight loss (RWL) in combat sports could pose additional risks. This case represents how routine cardiovascular screening during high-risk methods like RWL and high-intensity training (HIT) reveal abrupt ventricular arrhythmias in a young athlete. Case report: We report a case of a 20-year-old male wrestler athlete who developed disrupting arrhythmia during RWL and HIT. The study included: a medical exam, 12 lead electrocardiograms (ECG), transthoracic echocardiogram (ECHO), and 24 hours of continuous ECG monitoring in baseline, phase one (P1), (in which the athlete had to simulate RWL through vigorous training and dietary intervention and HIT) and phase two (P2), (with the same HIT protocol performed without the RWL procedure). Baseline laboratory analyses were without abnormalities, ECG showed sinus rhythm with one premature atrial contraction (PAC) and ECHO showed signs of concentric remodeling with preserved systolic, diastolic function, and global longitudinal strain. After P1 RWL simulation, he lost 5.15% of body weight in three days, which resulted in lower blood glucose levels, higher urea, creatinine, creatine kinase (CK), CK-MB levels, and slightly increased levels of NT pro-BNP, ECG revealed sinus rhythm with one ventricular premature beat (VPB), 24-hour continuous electrocardiogram (ECG) revealed frequent ventricular premature beats (PVB) 2150/ 24h, with 2 couplets, and 8 PAC. After an advised 4-week period of de-training continuous 24 hours, ECG monitoring was improved with only occasional PVB. The 24 hours continuous ECG monitoring was repeated after HIT and revealed even more frequent PVB, 5% of all beats for 24 hours, 4205 in total, and almost all VPB were in bigeminy and trigeminy. The athlete was advised against RWL and extremely vigorous exercise and for regular, frequent checkups with occasional ECG monitoring during and after exercise. Conclusion: The short and long-term implication of abrupt ventricular arrhythmias provoked by intensive training and methods like RWL is unknown. We postulate that cardiovascular screening is necessitated, especially during high-risk methods like RWL and HIT, in helping us prevent adverse outcomes and come to individual-based clinical making decisions for each athlete.